Acorane sesquiterpenes from the deep-sea derived Penicillium bilaiae fungus with anti-neuroinflammatory effects - Zhang, Wenfang; Meng, Qingyu; Wu, Jingshuai; Cheng, Wei; Liu, Dong; Huang, Jian; Fan, Aili; Xu, Jing; Lin, Wenhan (Frontiers in Chemistry, 2022)
Acorane-type sesquiterpenes comprise a unique class of natural products with a range of pharmaceutical effects. Genome sequencing and gene annotation, along with qRT-PCR detection, demonstrate that the deep-sea derived Penicillium bilaiae F-28 fungus shows potential to produce acorane sesquiterpenes. Chromatographic manipulation resulted in the isolation of 20 acorane sesquiterpenes from the large-scale fermented fungal strain. Their structures were established by the interpretation of spectroscopic data, together with X-ray diffraction, chemical conversion, and ECD data for configurational assignments. A total of 18 new sesquiterpenes, namely, bilaiaeacorenols A–R (1–18), were identified. Bilaiaeacorenols A and B represent structurally unique tricyclic acoranes. Compound 18 exhibited efficient reduction against NO production in LPS-induced BV-2 macrophages in a dose-dependent manner, and it abolished LPS-induced NF-κB in the nucleus of BV-2 microglial cells. In addition, marked reductions of iNOS and COX-2 in protein and mRNA levels were observed. This study extends the chemical diversity of acorane-type sesquiterpenoids and suggests that compound 18 is a promising lead for anti-neuroinflammation.